2001
DOI: 10.1001/archpedi.155.12.1298
|View full text |Cite
|
Sign up to set email alerts
|

To Be Rather Than Not To Be—That Is the Problem With the Questions We Ask Adolescents About Their Childbearing Intentions

Abstract: Asking sexually active teenagers about the strength of their intent to remain nonpregnant will make the results of office interviews and national surveys more useful because the responses such questions elicit will enable health care providers and policy makers to target common, modifiable antecedents of inconsistent contraceptive use for interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 15 publications
1
29
0
1
Order By: Relevance
“…Consistent with the work of Stevens-Simon, our data suggest that the majority of adolescent women are committed to not getting pregnant and that this commitment is generally associated with contraceptive behavior during the subsequent 3 months [10]. In fact, we found that two other questions about pregnancy intentions also predicted subsequent contraceptive behavior.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with the work of Stevens-Simon, our data suggest that the majority of adolescent women are committed to not getting pregnant and that this commitment is generally associated with contraceptive behavior during the subsequent 3 months [10]. In fact, we found that two other questions about pregnancy intentions also predicted subsequent contraceptive behavior.…”
Section: Discussionsupporting
confidence: 90%
“…Measuring pregnancy intentions to identify an at-risk population, particularly among adolescents, has been difficult [8,9]. Stevens-Simon et al proposed that asking about intentions to remain non-pregnant may better target young women at risk for pregnancy [10]. These questions asking about intentions to remain non-pregnant may be a more active question that demands that the patient critically evaluate her proactive behavior necessary to prevent pregnancy-the normal or default state for the sexually active woman.…”
mentioning
confidence: 99%
“…This notion is consistent with research showing that motivation to prevent additional childbearing is a more powerful antecedent of birth control use and subsequent fertility than is ambivalence about having another child. [43][44][45] …”
Section: Previous Research On Home Visiting Effects On Fertilitymentioning
confidence: 99%
“…Thus, explicit efforts to dispel the misperceptions about the opportunity costs of childbearing and burdens of prevention are needed. 6 By contrast, when the goal is STD prevention, there is no lack of motivation to avoid the consequences of unprotected sex, yet condom distribution programs have not curtailed the spread of these infections. 7 Many teenagers with conventional relationship goals think that the worst aspect of acquiring STDs is the psychological harm caused by the loss of trust and sel-respect.…”
Section: Introductionmentioning
confidence: 99%